Dark tourism destinations: the relationships between tourists' on-site experience, destination image and behavioural intention. Issue 2 (9th August 2021) - Qian, Lili; Zheng, Chunhui; Wang, Jinwei; Pérez Sánchez, María de los Ángeles; Parra López, Eduardo; Li, Hanliang
Abstract : Purpose: This study aims to explore how tourists construct destination images in the context of dark tourism and reveals the relationships between on-site experience, destination image and behavioural intention. Design/methodology/approach: The earthquake-ravaged county town of Beichuan in China was chosen as the study site. The study collected 298 viable questionnaires from tourists. Partial least squares structural equation modelling was performed to explore the relationships between the variables of on-site experience, destination image and behavioural intention. Findings: The study identified four dimensions of dark tourism destination image (TDI) from its attribute and functional perspective. It found that "image of memorial place" and "image of educational place" were the most perceptual images and positively related with most subdimensions of on-site experience and behavioural intention. "Image of leisure place" and "image of landscapes of fear" were less perceived by tourists and negatively related with some subdimensions of on-site experience and behavioural intention. Originality/value: To our knowledge, this study is the first attempt to explore the complex mechanisms of dark TDI formation with the framework of "on-site experiences–destination images–behavioural intentions". By identifying tourists' most and least perceptual images and their effective antecedents and consequences help to reconcile and manage the controversial and contradictory images of a dark tourism destination. Abstract : 黑色旅游地游客现场体验、目的地形象、行为意愿关系研究 摘要: 目标: 本文探讨了游客如何建构黑色旅游目的地形象, 进一步研究了游客现场体验、目的地形象、行为意愿之间的作用关系。 设计/方法: 以汶川地震重灾区北川老县城遗址为案例地, 本研究收集了游客结构化问卷298份, 采用偏最小二乘结构方程模型（PLS-SEM）分析了游客现场体验、目的地形象和行为意愿各维度之间的作用关系。 研究发现: 从目的地属性和功能角度, 本文区分了黑色旅游目的地形象四个维度。研究发现"纪念地形象"和"教育地形象"是游客感知最强的两大维度, 与绝大多数游客现场体验和行为意愿的维度呈显著正向影响关系。 "休闲地形象"和"恐惧景观形象", 游客感知较弱, 与现场体验和行为意向的一些维度呈负向影响关系。 创新/价值: 本文首次利用"现场体验-目的地形象-行为意愿"这一研究框架, 揭示黑色旅游目的地形象的复杂生成机制。通过识别游客感知最强和最弱的形象维度, 揭示其前因与后果, 有助于调和与管理有争议和矛盾的黑色旅游目的地形象。 Abstract : Destino de turismo oscuro: Relaciones entre las experiencias de los turistas en el lugar, imágenes del destino e intenciones de comportamiento Propósito: Este estudio explora cómo los turistas construyen la imagen del destino en el contexto del turismo oscuro, revelando las relaciones entre experiencias en el lugar, imágenes del destino e intenciones de comportamiento. Diseño/metodología/enfoque: El terremoto que devastó la ciudad del condado de Beichuan en China fue elegido lugar de estudio por sus peculiaridades para el desarrollo del destino oscuro. El estudio recopiló 298 cuestionarios viables de turistas. Se planteo un modelo de ecuaciones estructurales (PLS-SEM) para explorar las relaciones entre las variables de experiencias en el lugar, imágenes de destino e intenciones de comportamiento. Hallazgos: El estudio identificó cuatro dimensiones de la imagen del destino turístico oscuro desde su atributo y perspectiva funcional. De igual forma, se encontró que la "imagen del lugar conmemorativo" y la "imagen del lugar educativo" eran las imágenes más perceptivas y estaban relacionadas positivamente con la mayoría de los subdimensiones de las experiencias en el lugar e intenciones de comportamiento. Los turistas percibieron menos la "imagen de un lugar de ocio" y la "imagen de paisajes de miedo" y se relacionaron negativamente con algunos subdimensiones de las experiencias en el lugar e intención de comportamiento. Originalidad/valor: Hasta donde sabemos, este estudio es el primer intento de explorar el complejo mecanismo en la formación de TDIs oscuros con el marco de "experiencias en el lugar- imágenes de destino – intenciones de comportamiento". Al identificar las imágenes más o menos perceptivas de los turistas, y sus antecedentes y consecuencias efectivos, ayuda a conciliar y gestionar las imágenes controvertidas y contradictorias de un destino turístico oscuro.